Application of ferroelectrics to create electroluminescent indicators of temperature - Boyko, V.G.; Zayats, N.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
In this article, temperature dependences of brightness of thin film electroluminescent emitters (TFELE) based on metal-dielectric-semiconductor-metal (MDSM) structures with ceramic ferroelectric dielectric have been considered. Their comparable analysis with the temperature dependence of dielectric themself has been made. Literature data concerning this question have been briefly discussed. The conclusion about the possibility to use ferroelectrics (ceramics based on BaTiO₃, AlN, LiNbO₃) with a pronounced thermal dependence of capacitance characteristics to produce the temperature light indicators has been made. The design of a new temperature sensor can be realized in several ways. For example, in the form of the scales with a moving luminous column or separate lighting dots, depending on how clearly Curie peaks are observed on the temperature curves of dielectric permittivity.